Konflik Tokoh dalam Kaba Siumbuik Mudo - Charisma Pratama (Universitas Andalas, 2011)
This article describes character confict analysis of kaba Siumbuik Mudo. On this object, there is manjapuik malu or manjapuik baleh which reflect the main character’s pride. Using structural and qualitative method, the result shows that the main characters (Umbuik Mudo and Puti Galang Banyak) has high ego which brings conflicts on them.